Effect of a dynamic seat pan design on spine biomechanics, calf circumference and perceived pain during prolonged sitting. (November 2021) - Frey, M.; Barrett, M.; De Carvalho, D.
Abstract: This study investigates the effects of a dynamic seat pan design on sitting biomechanics, perceived pain and seat movement compared to a control. Thirty male participants were recruited for two experimental sessions consisting of a 2-h sitting exposure (standardized typing task). Spine angles, back muscle activity, perceived pain and calf circumference were measured pre and post exposure. Sitting in the dynamic condition resulted in lower pain ratings ( p  = 0.031), decreased calf circumference ( p  < 0.001), lower average seat pressure ( p  < 0.001), and greater seat contact area (p = 0.003) compared to the control. Spine angles and low back EMG for all 6 muscles showed no significant differences between chair conditions. These results suggest this dynamic seat pan design is effective at decreasing several negative components associated with sitting for the occupant. Future work should examine the longer-term effects of dynamic office chair features in the field setting with a more generalizable population. Highlights: A multiaxial seat pan design was compared to a standard office chair. The dynamic design facilitated movement and an anteriorly tilted seat pan. Lower increases in calf circumference and perceived pain were found. Participants rated the dynamic design higher than the standard chair. The multiaxial design tested might be beneficial to increase activity while seated.